Understanding students' intention and actual eco-friendly behavior: A qualitative research in University - Fang, Shyang-Chyuan (Technium Social Sciences Journal, 2021)
Universities can be considered a community because of their large population, large size and participation in many activities on campus. The behavior of these individuals has a direct or indirect impact on environmental sustainability. Because of environmental problems, many universities focus on achieving sustainable development in terms of educational effectiveness. This study investigated the environmental intention and actual behavior of students in two schools. Penetrating many studies have used different theories for eco-friendly behavior, and this study uses the theory of planned action. In order to understand the students' intentions and environmental behavior, 20 students were interviewed through the survey from two universities. The results were made up of six themes (behavioral intention, environmental knowledge, environmental well-being, environmental attitude, social and cultural norms, and environmental behavior), found that current research on the forecasting framework has shaped the student's perspective to identify themes related to intention and actual green behavior.